2008
DOI: 10.3732/ajb.2007364
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in salt tolerance traits allows for invasion of novel habitat by Japanese knotweed s. l. (Fallopia japonica and Fbohemica, Polygonaceae)

Abstract: Japanese knotweeds are among the most invasive organisms in the world. Their recent expansion into salt marsh habitat provides a unique opportunity to investigate how invasives establish in new environments. We used morphology, cytology, and AFLP genotyping to identify taxa and clonal diversity in roadside and salt marsh populations. We conducted a greenhouse study to determine the ability to tolerate salt and whether salt marsh populations are more salt tolerant than roadside populations as measured by the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(146 citation statements)
references
References 98 publications
5
137
4
Order By: Relevance
“…These classic predictions are intuitive and often supported empirically (e.g., Clausen, Keck, & Hiesey, 1948). However, in some cases, data across a diversity of taxa show either no association of genetic differences with habitat (e.g., Richards, Hamrick, Donovan, & Mauricio, 2004; Foust et al., 2016; examples in Schmidt et al., 2008) or that low levels of molecular diversity are not associated with decreased phenotypic variation (Dlugosch & Parker, 2008; Richards et al., 2008). The disconnect between empirical findings and ecological theory suggests the possibility of additional, underexplored molecular mechanisms, such as epigenetic modifications, that mediate the relationship between phenotype and environment.…”
Section: Introductionmentioning
confidence: 99%
“…These classic predictions are intuitive and often supported empirically (e.g., Clausen, Keck, & Hiesey, 1948). However, in some cases, data across a diversity of taxa show either no association of genetic differences with habitat (e.g., Richards, Hamrick, Donovan, & Mauricio, 2004; Foust et al., 2016; examples in Schmidt et al., 2008) or that low levels of molecular diversity are not associated with decreased phenotypic variation (Dlugosch & Parker, 2008; Richards et al., 2008). The disconnect between empirical findings and ecological theory suggests the possibility of additional, underexplored molecular mechanisms, such as epigenetic modifications, that mediate the relationship between phenotype and environment.…”
Section: Introductionmentioning
confidence: 99%
“…First, as FJ does not display genetic variation in Europe (Mandak et al 2004;Krebs et al 2009) any phenotypic variation must by definition have an environmental basis. Large phenotypic plasticity may be a key attribute of FJ (Richards et al 2008). Higher values of ramification rate and lower SLA in the site JJM compared to VER are ascribable to contrasting light conditions.…”
Section: Variation Amongst Sites and Yearsmentioning
confidence: 99%
“…Their rhizome system is very dense and can grow to 2 meters in depth [17]. Recent studies have shown that, apart from extensive vegetative growth, hybridization between the F. japonica and F. sachalinensis has created even more highly invasive genotypes of the hybrid F. ×bohemica that are able to establish themselves by seed [15,18,19].…”
Section: Introductionmentioning
confidence: 99%